PEMBENTUKAN SENYAWA MALTODEKSTRIN DARI PATI BENGKUANG (Pachyrhizus erosus L.) MELALUI HIDROLISIS ENZIM α-AMILASE - Liano, Ireniza; Herdyastuti, Nuniek (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Surabaya State University, located at Jl Ketintang, Surabaya, East Java, Indonesia, 2024)
Jicama (Pachyrhizus erosus L.) is one of the tubers with potential as a starch source. Starch can be hydrolyzed into maltodextrin compound using α-amylase enzyme. This study aims to determine how the effect of the addition of starch weight and the length of hydrolysis time on the formation of maltodextrin compounds by manipulating the addition of bengkuang starch weight with a mass of 5, 10, 15, 20, and 25g and the length of α-amylase enzyme hydrolysis time for 100, 120, 140, 160 and 180 minutes with the α-amylase enzyme adding 20% (w/v). The results showed that the addition of 20 grams of bengkuang starch weight obtained a yield of 70.47%; dextrose equivalent value of 12.56; and residual starch content of 42.13%. The length of time for hydrolysis of jicama starch for 180 minutes produced a yield of 72.45%; dextrose equivalent value of 15.81; and residual starch content of 26.01%. Based on the results obtained, it shows that the addition of weight of jicama starch and the length of time for hydrolysis using the α-amylase enzyme affect the dextrose equivalent value of maltodextrin.